The Role of Meditation in Enhancing Athlete Performance During High-Pressure Conditions - Hossain, Rezwan; azad, abul kalam; Khatun, Halima (International Journal of Arts, Sciences and Education, 2026)
Background: University-level athletes often experience performance deterioration under pressure due to anxiety and attentional lapses, yet psychological support remains limited. Objective: This study investigated whether a 4-week structured meditation program improves penalty-shooting accuracy and reduces anxiety in male university football players during simulated high-pressure conditions. Methods: Using a single-group pre-test/post-test quasi-experimental design, 40 male football players (aged 20–25) from Jashore University of Science and Technology, Bangladesh, underwent 16 sessions (45 min each, 4×/week) of a standardised meditation protocol—including diaphragmatic breathing, Anulom-Vilom pranayama, guided imagery, and mindfulness meditation—followed by identical penalty-shooting assessments before and after. Results: Mean penalty accuracy improved significantly from 3.10 ± 0.79 (pre) to 3.65 ± 0.95 (post), Z = −4.12, p < 0.001, with a large effect size (r = 0.65). Inter-rater reliability was excellent (κ = 0.96). Conclusion: Brief, structured meditation training enhances performance stability and psychological readiness, supporting its integration into routine sport psychology programming—especially for non-elite or resource-constrained athletic settings. Grounded in the Mindfulness-Acceptance-Commitment (MAC) model, this low-cost intervention offers scalable mental skill development.